Addressing Words Shifting by Angkola Society at Padangsidimpuan - Sari, Siti Meutia; Mahrani, Mahrani (English Department, University of Riau Kepulauan, Batam,Indonesia, 2018)
This research aims to find the form of greeting words which has shifted of Angkola people in Padangsidmpuan, to find the factors that influence shifting of greeting words ofv Angkola people in Padangsidimpuan. The theory which is used for this research is according to Fashold theory in concept Angkola people greeting words â€œSurat Tumbaga Holingâ€and the factors of language shifting of Fashold theory.Â This research was conducted by appliying descriptive qualitative method. The subjects of this research is Angkola people in Padangsidimpuan from first generation (40-50 years old), second generation (17-35 years old), third generation (6-15 years old). The finding of this research showed that the shifting of greeting words was occur in Angkola people in Padangsidimpuan and the most shifting occur in second and third generation that influence by three factors, such as: 1)Migrant communities, 2) Economic and 3) Education in Padangsidimpuan